Body mass index and blood pressure in adolescents from an urban area in Mexico: Índice de masa corporal y presión arterial en adolescentes de zonas urbanas en México - Delgadillo Castañeda, Rodolfo (2024)
Introduction: The changes brought about by the COVID-19 pandemic in adolescent activities have affected recreational aspects due to limited contact to prevent virus spread. This has contributed to increased indicators of overweight and obesity and could impact blood pressure levels.Objective: To determine the degree of association between Body Mass Index (BMI) and systemic blood pressure in adolescents.Methods: Systemic blood pressure was measured using continuous ambulatory blood pressure monitoring over 24 hours (ABPM). The sample consisted of 42 high school students with similar urban geographic characteristics in Mexico. All participants underwent anthropometric evaluation to identify notable group characteristics. The correlation was assessed using Spearman's Rho test.Results: Of the 42 participants included, 28.5% showed obesity, 21.45% were overweight, and no patient had hypertension. However, 23.8% showed prehypertension. A significant correlation was evidenced between BMI and both systolic and diastolic blood pressure values, at 0.390 and 0.382, respectively (p-value: 0.013 and 0.015, respectively).Conclusion: BMI was significantly associated with systolic and diastolic blood pressure levels in adolescents from an urban area in Mexico.